Preparation and characterization of nanopowder of Acalypha hispida Leaves Extract Using Planetary Ball Milling - Hamzah Alfarisi; Siti Sa'diah; Berry Juliandi; Tutik Wresdiyati (Molekul, 2022)
Acalypha hispida Burm.f. is commonly used as an ornamental plant known for pharmacological effects. The nanoscale extract increases bioavailability and bioactivity. This research aimed to produce and characterize nanopowder extract of A. hispida leaves. Powdered leaves were macerated in 96% ethanol, then was evaporated in the spry dryer. Nanopowder extract was produced using planetary ball milling at 5000 rpm in different milling times, namely 5 minutes (nanopowder A), 10 minutes (nanopowder B), and 40 minutes (nanopowder C). The nanopowder extracts were evaluated using a particle size analyzer, scanning electron microscope, and high-performance liquid chromatography. The average particle size of A. hispida crude extract was 1271 nm, and nanopowder A, B, and C respectively were 837.1 nm, 803.8, and 512.2 nm. The polydispersity index of A. hispida crude extract, nanopowder A, B, and C were 0.754, 0.696, 0.717, dan 0.612. The milling process for 40 minutes reduced the content of 5% gallic acid and 10.3% catechin. The SEM image of nanopowder C was smaller than crude extract. The best average particle size of nanopowder C (512.2 nm) and polydispersity index (0.612) were produced using PBM for 40 minutes at 5000 rpm.